1999
DOI: 10.1063/1.479852
|View full text |Cite
|
Sign up to set email alerts
|

Generation and observation of GHz ultrasonic waves on liquid surfaces and a liquid/liquid interface by transient reflecting grating method

Abstract: We optically generated and observed GHz ultrasonic waves on liquid surfaces and a liquid/liquid interface for the first time using the transient reflecting grating (TRG) method. Four kinds of samples were used for measurement of the surfaces; two types of black ink, an aqueous solution of crystal violet (CV aq solution) and ethanol aqueous solutions of CV. A cyclohexane/CV aq solution interface was used for measurement of the liquid/liquid interface. The 0.7 GHz and 0.6 GHz ultrasonic waves were generated on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
1
11
0
1
Order By: Relevance
“…At high temperatures, when the material has reached a liquid state, capillary forces become dominant, so that information about the surface tension can be extracted from the propagation characteristics of capillary waves. In this regime, the technique is an extension of the technique reported by Yasomoto et al [11,12] and compatible to the results obtained by Ikeda et al [13] and Behroozi et al [14,15].…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…At high temperatures, when the material has reached a liquid state, capillary forces become dominant, so that information about the surface tension can be extracted from the propagation characteristics of capillary waves. In this regime, the technique is an extension of the technique reported by Yasomoto et al [11,12] and compatible to the results obtained by Ikeda et al [13] and Behroozi et al [14,15].…”
Section: Introductionsupporting
confidence: 88%
“…ISS is a technique that has proven its value for the thermal and elastic characterization of bulk solids [26], thin coatings [27], intermediate layers in multilayered systems [28], bulk fluids [4], fluid-solid interface [6], and the free liquid surface [11][12][13]29]. In the employed ISS scheme shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…ISS studies of surface acoustic waves (SAWs) originally focused largely on supported [8,9] and unsupported [10] thin films. ISS studies have also been reported for liquid/liquid interface acoustic modes [7], as well as surface acoustic modes in thin metallic films supported on anisotropic crystalline semiconductor substrates [12]. More recently orientationally resolved ISS studies have been performed on crystalline surfaces as a probe of the elastic constants of metals and semiconductors [14].…”
Section: Introductionmentioning
confidence: 96%
“…A number of studies have demonstrated impulsive stimulated scattering (ISS) [1,2] as a probe of the surface acoustic properties of solids, liquids, thin films, and condensed phase interfaces [3][4][5][6][7][8][9][10][11][12][13]. ISS studies of surface acoustic waves (SAWs) originally focused largely on supported [8,9] and unsupported [10] thin films.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Finally, the transient reflecting grating technique is a four-wave mixing method that probes the photoinduced changes of reflectivity of the interface. 6,7 The main drawback of all these techniques is the impossibility to have a control of the thickness of the probed region. Consequently, the depth profile of a given property cannot be investigated.…”
Section: Introductionmentioning
confidence: 99%